Challenges of Implementing E-Learning in Upper Elementary Education: Perspectives of Abu Al-‘Arqan School Teachers, South Hebron - Daraweesh, Hiyam Yousssef; Arman, Ibrahim Mohammad (Journal of Educational and Psychological Sciences, 2024)
This study aimed to uncover the facing teachers of upper elementary stage in employing e-learning from the perspective of teachers at Abu Al-Arqan Mixed Primary School in the Directorate of Education in South Hebron. To achieve this, the researcher adopted a qualitative method to conduct the study (through employing the interview method) to collect detailed data and achieve a deeper understanding of the issue. The researcher conducted interviews with 8 male and female teachers at Abu Al-Arqan Mixed Primary School in the Directorate of Education in South Hebron in the second semester of the academic year (2023-2024). The authenticity and reliability of the interviews were verified using appropriate methods. The results showed that there are many obstacles and challenges that hinder the use of e-learning by teachers and students. The results also showed that these challenges are distributed across several dimensions (material, technological, cognitive, skill-related, and psychological). The study recommended the need to support the infrastructure of e-learning, provide qualified human resources, internet networks, and communications. The researcher also recommended the need to hold workshops and training programs to equip teachers with e-learning strategies and raise awareness among parents and students about the importance of e-learning and encourage them to utilize it.
Keywords: e-learning; upper primary stage